#TITLE_ALTERNATIVE# - ADIPRADANA (NIM : 13706059); Pembimbing : Dr.Ir.Husaini Ardy, NUGRAHA
Compressor blade is a component of a power plant that exposed to a high temperature. To comply to those condition, a martensitic stainless steel such as X11CrNiMo12 is often used as a base material for a compressor blade. Even though itÃ‚Â’s sufficient in terms of technical specification, X11CrNiMo12 may fail. To investigate them, a micro structural change after the material is exposed at high temperature is observed. This experiment will focus on observing micro structural change of two pieces of X11CrNiMo12 material using different heating time and heating temperature parameters. There will be three heating temperature and three heating time that will be used to produce nine combinations of heating temperature and heating time. The effect of heating temperature and heating time will be observed by examine the microstructural changes and its correlation with hardness and tensile strength of the corresponding material. Hollomon-Jaffe parameter will be used to predict the hardness of material affected by heating temperature-heating time parameters. Micro structural changes of X11CrNiMo12 material after heating shows a formation of ferrite phase from a decomposed martensite phase which lowered the hardness and tensile strength of the material. The lowest hardness value for two blade occurred at 500oC-24 hours parameter, and the value are 26,28 HRC and 27,42 HRC for R1-14 and R5-13 sample respectively. The lowest tensile strength are 985,29 MPa and 970,68 MPa for R1-14 and R5-13 sample respectively. According to calculation results using Hollomon-Jaffe equation, it is found that the remaining lifetime for these two blades material is 4620,68 hours for R1-14 sample, and 3704,545 hours for R5-13 sample.